Binge eating and other eating-related problems in adolescents undergoing gastric bypass: results from a Swedish nationwide study (AMOS). (1st August 2018) - Järvholm, Kajsa; Olbers, Torsten; Peltonen, Markku; Marcus, Claude; Dahlgren, Jovanna; Flodmark, Carl-Erik; Henfridsson, Pia; Gronowitz, Eva; Karlsson, Jan
Abstract: Bariatric surgery is established as a treatment option for adolescents with severe obesity. Little is known about binge eating (BE) and other eating-related problems in adolescents undergoing bariatric surgery. BE, emotional eating, uncontrolled eating, and cognitive restraint were assessed at baseline, and one and two years after gastric bypass using questionnaires in 82 adolescents (mean age 16.9 years, 67% girls). BE was assessed with the Binge Eating Scale (BES) and other eating-related problems with the Three Factor Eating Questionnaire. Change in eating-related problems over time, along with the relationship between eating behaviors and other aspects of mental health and weight outcome, were analyzed. At baseline, 37% of the adolescents reported BE (defined as a BES score >17). Two years after gastric bypass, adolescents reported less problems related to BE, emotional eating, and uncontrolled eating. Improvements were moderate to large. Adolescents reporting BE at baseline also reported more general mental health and psychosocial weight-related problems before and/or two years after surgery, compared to adolescents with no BE. After surgery adolescents with BE before surgery reported more suicidal ideation than those with no BE at baseline. None of the eating-related problems assessed at baseline was associated with weight outcome after surgery. More binge eating, emotional eating, and uncontrolled eating two years after surgery were associated with less weight loss. In conclusion, eating-related problems were substantially reduced in adolescents after undergoing gastric bypass. However, pre-operative BE seem to be associated with general mental health problems before and two years after surgery, including suicidal ideation. Pre-operative eating-related problems did not affect weight outcome, and our results support existing guidance that BE should not be considered an exclusion criterion for bariatric surgery in adolescents.